Health Related Quality of Life in Interstitial Lung Disease: Can We Use the Same Concepts Around the World? - Aronson, Kerri I.; Suzuki, Atsushi (Frontiers in Medicine, 2021)
Health-Related Quality of Life (HRQOL) is increasingly viewed as an important patient-centered outcome by leading health organizations, clinicians, and patients alike. This is especially true in the interstitial lung disease community where patients often struggle with progressive and debilitating disease with few therapeutic options. In order to test the effectiveness of new pharmacologic therapies and non-pharmacologic interventions globally in ILD, this will require expansion of clinical research studies to a multinational level and HRQOL will be an important endpoint to many. In order to successfully expand trials across multiple nations and compare the results of studies between different communities we must recognize that there are differences in the concepts of HRQOL across the world and have strategies to address these differences. In this review, we will describe the different global influences on HRQOL both generally and in the context of ILD, discuss the processes of linguistic translation and cross-cultural adaptation of HRQOL Patient Reported Outcome Measures (PROMs), and highlight the gaps and opportunities for improving HRQOL measurement in ILD across the world.